Bilateral sacroiliitis: a rare cause for a common presentation - Mahto, Subodh Kumar; Singh, Praveen Kumar; Sheoran, Ankita; Jamal, Afroz; Agarwal, Nagina (International Journal of Research in Medical Sciences, 2018)
Fever and osteoarticular involvement of axial skeleton are hallmark clinical manifestations of brucellosis but other diseases like ankylosing spondylitis, tuberculosis, Paget’s disease of bone, sarcoidosis should also be considered as differential diagnosis. Brucellosis is an uncommon infectious disease in India. Signs and symptoms of the disease are highly variable, with musculoskeletal complaints occurring frequently. Authors hereby reported a case of brucellosis presenting with fever, polyathralgia, bilateral sacroiliitis and enthesitis. Knowledge of geographical distribution, evidence of exposure to the cattle and a high degree of clinical suspicion of brucellosis are very important for early differentiation from other diseases to prevent lethal complications and institute early treatment and a prompt recovery.